New Distributional Records of Lichens for the State of Mizoram, Indo-Burma Region of India - Thangjam, Nurpen Meitei; Kumar, Awadhesh; Laldingliani, Tbc; Upreti, Dalip Kumar (Trends in Sciences, 2022)
The present paper enumerated the occurrence of 30 different species of lichens collected from 2 different study sites situated in 2 districts of Mizoram. It included Crustose (12 sp.), Foliose (16 sp.) and Fruticose (2 sp.) along with 9 species named as Diploschistes scruposus (Schreb.) Norman, Diorygma macgregorii (Vain.) Kalb, Staiger & Elix, Diorygma soozanum (Zahlbr.) M. Nakan. & Kashiw., Malmidea granifera (Ach.) Kalb, Rivas Plata & Lumbsch, Letrouitia vulpina (Tuck.) Hafellner & Bellem., Parmotrema austrosinense (Zahlbr.) Hale, Parmotrema crinitoides J.C. Wei, Parmotrema nilgherrense (Nyl.) Hale, Parmotrema rampoddense (Nyl.) Hale reported as a new record for the 1st time to the state of Mizoram, Northeast India. The finding were correlated with other previous reports on lichens and it provided detailed overview of documentation, distribution and diversity of lichens found in the small state like Mizoram under Indo-Burma region. Therefore, the richness of lichen diversity indicates the conditions of good forest health in Mizoram. The study also submits the need of conservation and exploration in the unexplored areas. HIGHLIGHTS The insight of the lichens diversity of the Mizoram state now provides the open platform for Lichenologist as well as Environmentalist The report of few species for the first time from the forest dominated hilly region of Mizoram had shown the richness of lichen distribution and its diversity As urbanisations as well as infrastructures developments are taking places in the remote corner of the state, it is very essential to explore the lichens diversities GRAPHICAL ABSTRACT